Optical Communication Engineering Simulation Laboratory for Effective Undergraduate Education during Era of Covid19 - et. al., Shailesh Khant, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Corona virus pandemic COVID19 has greatly affected the education sector. All academics institutes have to shut off face to face classroom teaching and learning. Engineering education, where there is a need to understand more of the practical concepts using costly hardware is greatly affected. One such engineering course, which involves this type of hardware, it requires practical understanding, is optical communication engineering. This paper describes how effectively this course will be taught from home using simulation tool. OPTSIM 5.0TM simulation tool is used to simulate all basic and advanced optical systems. Various optical systems and experiments such as Optical receiver, Optical Transmitter, Optical fiber amplifiers, Optical MUX, Optical De-MUX etc. can be designed for various fiber parameters and performance is measured using BER analyzer, Eye diagram analyzer, Optical Monitor, spectrum analyzer etc. This paper also describes how effectively the benefits of optical system and its performance using OPTSIM 5.0TM software will be taught in the virtual environment of teaching and learning.